In Vitro Anticataract Activity of Zingiber officinale on Goat Lenses - Kumar, Manish (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The antioxidants such as Zingiber officinale and Enalapril (ACE Inhibitor) were subjected to prevent cataract formation in vitro on glucose induced cataract model. Goat lenses were incubated in artificial aqueous humor containing 55 mM glucose (cataractogenesis) with enalapril and Zingiber officinale extract in different concentrations at room temperature for 72 h. Biochemical parameters studied in the lens were electrolytes (Na+, K+), Na+-K+-ATPase activity, malondialdehyde (MDA) and proteins. Glucose induced opacification of goat lens began 8-10 hrs after incubation and was complete in 72-80 hrs. Cataractous lenses showed higher Na+, MDA (P<0.001), lower Na+-K+-ATPase activity, and water-soluble protein content. Lenses treated with enalapril 5ng/ml and Zingiber officinale extract in concentrations of 100, 300, and 500 ng/ml showed higher protein (total and water soluble proteins) content and prevented formation and progress of cataract by glucose, as evidenced by biochemical parameters. Key words: Antioxidants, Zingiber officinale, Free radicals, Anticataract